Exploration and Evaluation of Bilingual Learning of Geography - Meyer, Christiane (Journal of Geography Education, 2004)
Research in bilingual programmes is "en vogue". Scientists investigate the peculiarities and problems of bilingual teaching. In this context the following article presents some results of the author's thesis, i.e. the exploration and evaluation of bilingual learning of geography from a geographical point of view. First the article gives a review ofthe contents and scientific questions of this thesis. After that a few results of the research are presented. The empirical studies investigate the importance, perception and assessment of the bilingual geography learning at grammar schools from the point of view of the learners, using both quantitative and qualitative methods. The first part of the surveys is based on a questionnaire. The second one supports the results of the questionnaire by the description of subjective theories. These subjective theories are based on interviews. In this case the main emphasis lies on the description of two subjective theories. Finally some essential conclusions of the studies are pointed out.